A chain folding regular structure anion exchange membrane and preparation method thereof
By designing an anion exchange membrane with a regular chemical structure and using a chain folding structure to form a highly regular ion channel, the problem of difficult balance between conductivity and selectivity in the existing technology is solved, and efficient ion transmission and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202211246720.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The existing ion exchange membranes are difficult to balance between conductivity and selectivity, and the entangled state between traditional polymer molecules makes it difficult to achieve the construction of regular controllable ion channels.
By designing an anion exchange membrane with a regular chemical structure, Friedel–Crafts polymerization of alkyl derivatives and ketone monomers is used to form polymer segments with chain folding structures, and highly regular ion channels are formed through annealing.
Efficient ion selective transmission is achieved, the conductivity can reach more than 30mS/cm, the selectivity can reach more than 100, and the tensile strength can reach more than 30MPa.
Smart Images

Figure BDA0003886958140000021 
Figure BDA0003886958140000022 
Figure BDA0003886958140000023
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion exchange membranes, and in particular relates to an anion exchange membrane with a regular chain folding structure and a preparation method thereof. Background Art
[0002] Energy shortages and environmental pollution are serious obstacles to the development of human society today. To address these challenges, people are increasingly focusing on the development and application of green, clean energy and environmental treatment technologies, such as flow batteries, fuel cells, water electrolysis for hydrogen production, electrodialysis, and ion separation. Ion exchange membranes are key materials required for these technologies, selectively transporting specific ions. Their performance directly impacts the efficiency and lifespan of the devices used.
[0003] Currently, the design and development of ion exchange membranes faces the challenge of balancing conductivity and selectivity. To overcome these limitations, one effective approach is to design and construct highly regular and controllable ion transport channels, thereby reducing the ion transport path and achieving selective ion transport by regulating the channel size. For a long time, research on the construction of ion exchange membranes and ion transport channels has mainly focused on forming hydrophilic and hydrophobic microphase separation structures in polymer membranes through structural design, thereby forming ion transport channels. However, this molecular self-assembly behavior driven solely by the polarity difference between the main and side chains is usually weak and difficult to control, making it difficult to form regular and controllable ion transport channels. At the same time, the chaotic and amorphous entanglement state between traditional polymer molecules also makes it difficult to construct regular and controllable ion channels. Summary of the Invention
[0004] The purpose of the present invention is to provide an anion exchange membrane with a regular chain folding structure and a preparation method thereof. The anion exchange membrane of the present invention has a regular crystalline structure, and the ion exchange groups are arranged on the periphery to form highly regular and controllable ion channels.
[0005] The present invention provides an anion exchange membrane with a regular chain folding structure, which is formed from a casting solution and then annealed;
[0006] The casting solution includes a functionalized polymer having a structure shown in Formula 1,
[0007]
[0008] In formula I, x is an integer from 5 to 30, and n is a positive integer from 10,000 to 100,000;
[0009] R is selected from one of Formulas 2 to 6, and r is an integer from 1 to 10;
[0010]
[0011] Q is selected from one of quaternary ammonium salts, quaternary phosphonium salts, imidazole salts, piperidinium salt cations and their derivatives.
[0012] The present invention provides a method for preparing an anion exchange membrane having a regular chain folding structure as described above, comprising the following steps:
[0013] A) polymerizing an alkyl derivative having a structure of Formula 7 and a ketone monomer by a Friedel-Crafts reaction in the presence of a first solvent and a superacid catalyst to obtain an initial polymer;
[0014]
[0015] In formula 7, x is an integer from 5 to 30;
[0016] B) mixing the initial polymer, the second solvent, the cationic functionalized small molecule and the acid binding agent to perform a functionalization reaction to obtain a functionalized polymer;
[0017] C) dissolving the functionalized polymer in a third solvent to form a casting solution, coating the casting solution to form a membrane, and annealing to obtain an anion exchange membrane with a regular chain folding structure.
[0018] Preferably, the ketone monomer is one or more of N-methyl-4-piperidone, 2,2,2-trifluoroacetophenone, indole ketone and 1,1,1-trifluoroacetone, and derivatives thereof;
[0019] The first solvent is one or more of dichloromethane, chloroform, and 1,2-dichloroethane;
[0020] The catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid.
[0021] Preferably, the molar ratio of the alkyl derivative to the ketone monomer is 1:(1-1.5); the volume ratio of the first solvent to the superacid catalyst is (0-3):1, and the ratio of the total molar amount of the alkyl derivative and the ketone monomer to the volume of the first solvent is (0.3-1) mol:100 mL.
[0022] Preferably, the polymerization temperature in step A) is -10 to 30° C., and the polymerization time is 2 to 100 hours.
[0023] Preferably, the second solvent is one or more of N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide and N-methylpyrrolidone;
[0024] The cationic functionalized small molecule is one or more of iodomethane, trimethylamine, N-methylimidazole and N-methylpiperidine;
[0025] The acid binding agent is one or more of anhydrous potassium carbonate, triethylamine, pyridine and diisopropylethylamine.
[0026] Preferably, the molar ratio of the initial polymer to the cationic functionalized small molecule is (0.5-1):1; the molar ratio of the acid binding agent to the cationic functionalized small molecule is (1-4):1.
[0027] Preferably, the temperature of the functionalization reaction in step B) is 25 to 120° C.; and the time of the functionalization reaction in step B) is 1 to 3 days.
[0028] Preferably, the third solvent includes one or more of N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide and N-methylpyrrolidone;
[0029] The concentration of the casting solution is 0.005-0.2 g / mL.
[0030] Preferably, the annealing temperature is 60-120° C.; and the annealing time is 1-5 hours.
[0031] The present invention provides an anion exchange membrane with a regular chain-folding structure, obtained by forming a membrane from a casting solution followed by annealing. The casting solution comprises a functionalized polymer having the structure shown in Formula 1. An anion exchange membrane with a regular chemical structure is designed and prepared by using an alkyl derivative with a certain number of methylene groups between two benzene rings as a monomer, which is then reacted with a ketone monomer via a Friedel–Crafts polymerization reaction. This anion exchange membrane has a fixed-length alkyl chain spacing between each functional unit. This regular chemical structure imparts unique chain-folding self-assembly behavior to the polymer segments. During the film-forming process, which is followed by solvent evaporation and curing, and annealing, the alkyl segments contained in the polymer segments spontaneously fold under the influence of crystallization, self-assembling into a regular chain-folding structure. Clear lattice fringes can be observed under high-resolution transmission electron microscopy. Furthermore, tests such as small-angle X-ray scattering and atomic force microscopy revealed that, due to differences in polarity, the functional groups are distributed around the periphery of the chain-folding structure, forming highly regular ion transport channels, enabling selective and efficient ion transport. In addition, by changing the chemical structure such as the length of the spacer alkyl chain, the length of the side chain, the type of functional group, etc., the morphology, size and function of the ion channel can be regulated. - The ion conductivity can reach over 30mS / cm, which is twice as high as the commercial anion exchange membrane AMV currently on the market. + and Mg 2+ The selectivity can reach more than 100, and the tensile strength can reach more than 30MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0033] Figure 1 Schematic diagram of the formation of chain folding regular structure and regular ion channel of the present invention;
[0034] Figure 2 High-resolution transmission electron microscopy characterization of the anion exchange membrane obtained in Example 1 of the present invention;
[0035] Figure 3 Atomic force microscopy characterization of the anion exchange membrane obtained in Example 1 of the present invention;
[0036] Figure 4 The mechanical properties of the anion exchange membrane obtained in Example 1 of the present invention;
[0037] Figure 5 This is a temperature-increasing conductivity test of the anion exchange membrane obtained in Example 1 of the present invention;
[0038] Figure 6 The anion exchange membrane obtained in Example 1 of the present invention is K + and Mg 2+ Flux and selectivity of transmembrane transport. DETAILED DESCRIPTION
[0039] The present invention provides an anion exchange membrane with a regular chain folding structure, which is formed from a casting solution and then annealed;
[0040] The casting solution includes a functionalized polymer having a structure shown in Formula 1,
[0041]
[0042] In Formula I, x is an integer from 5 to 30, such as 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, preferably a range with any of the above values as the upper or lower limit; n is a positive integer between 10,000 and 100,000;
[0043] R is selected from one of Formulas 2 to 6, r is an integer from 1 to 10, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, preferably a range value with any of the above values as the upper or lower limit; the length of the side chain will affect the size of the formed ion channel, and too long a side chain will reduce the regularity of the structure.
[0044]
[0045] Q is selected from quaternary ammonium salts, quaternary phosphonium salts, imidazole salts, piperidinium salts and their derivatives. Preferably, Q can be any one of formulas 7 to 9.
[0046]
[0047] The thickness of the anion exchange membrane in the present invention is preferably 5 to 500 μm.
[0048] The schematic diagram of the chain folding regular structure and regular ion channel formed by the present invention is as follows Figure 1 As shown, each functionalized unit of the prepared anion exchange membrane has a spacer alkyl chain of the same length. During the membrane formation and annealing process, the spacer alkyl chains fold and stack together to form a regular chain folding structure. Due to the polarity difference between the functionalized groups and the alkyl chains, the functionalized groups are arranged on the periphery of the chain folding structure and aggregate with each other to form regular ion channels, realizing efficient ion selective transport.
[0049] The present invention also provides a method for preparing an anion exchange membrane with a regular chain folding structure, comprising the following steps:
[0050] A) polymerizing an alkyl derivative having a structure of Formula 7 and a ketone monomer by a Friedel-Crafts reaction in the presence of a first solvent and a superacid catalyst to obtain an initial polymer;
[0051]
[0052] In formula 7, x is an integer from 5 to 30;
[0053] B) mixing the initial polymer, the second solvent, the cationic functionalized small molecule and the acid binding agent to perform a functionalization reaction to obtain a functionalized polymer;
[0054] C) dissolving the functionalized polymer in a third solvent to form a casting solution, coating the casting solution to form a membrane, and annealing to obtain an anion exchange membrane with a regular chain folding structure.
[0055] The present invention prepares an alkyl derivative monomer and a ketone monomer having benzene ring substituents at both ends and a certain number of methylene groups in between, dissolves them in a first solvent, adds a super acid catalyst in an ice-water bath, and then performs a nucleophilic addition condensation reaction through a Friedel-Crafts reaction to obtain an initial polymer.
[0056] In the present invention, the alkyl derivative monomer has a structure as shown in Formula 7, where x is an integer from 5 to 30, such as 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, preferably a range value with any of the above values as the upper or lower limit; too few methylene groups will make it difficult to form a chain folding structure, and the more methylene groups there are, the lower the required reaction temperature and the longer the reaction time, while too many methylene groups will result in insufficient molecular weight of the polymer.
[0057] The ketone monomer is one or more of N-methyl-4-piperidone, 2,2,2-trifluoroacetophenone, indole and 1,1,1-trifluoroacetone, as well as derivatives of the above ketone monomers; the ketone monomer carries a -Cl, -Br or -I group, which can react with a cationic functionalized small molecule; the first solvent is one or more of dichloromethane, chloroform and 1,2-dichloroethane; and the catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid.
[0058] In the present invention, the molar ratio of the alkyl derivative to the ketone monomer is 1: (1 to 1.5), more preferably 1: (1.1 to 1.4), such as 1: 1, 1: 1.1, 1: 1.2, 1: 1.3, 1: 1.4, 1: 1.5, preferably with any of the above values as the upper or lower limit of the range; the volume ratio of the first solvent to the superacid catalyst is (0 to 3): 1, more preferably (0.5 to 2.5): 1, such as 0.1: 1, 0.5: 1, 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1, preferably with any of the above values as the upper or lower limit of the range. The range value of the lower limit; the ratio of the total molar amount of the alkyl derivative and the ketone monomer to the volume of the first solvent is (0.3~1) mol:100mL, more preferably (0.4~0.6) mol:100mL, such as 0.3mol:100mL, 0.4mol:100mL, 0.5mol:100mL, 0.6mol:100mL, 0.7mol:100mL, 0.8mol:100mL, 0.9mol:100mL, 1mol:100mL, preferably a range value with any of the above values as the upper or lower limit.
[0059] In the present invention, the polymerization temperature is preferably -10 to 30°C, more preferably -5 to 25°C, such as -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, and preferably a range value with the above arbitrary numerical values as the upper or lower limit; the polymerization time is preferably 2 to 100 hours, more preferably 10 to 80 hours, such as 2 hours, 5 hours, 10 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours, 70 hours, 80 hours, 90 hours, 100 hours, and preferably a range value with the above arbitrary numerical values as the upper or lower limit.
[0060] After obtaining the initial polymer, the present invention adds the initial polymer to a second solvent and, after the initial polymer is fully dissolved, forms an initial polymer solution. A cationic functionalized small molecule and an acid-binding agent are added to the solution to carry out a functionalization reaction. The reactant is purified and dried to obtain an anionic functionalized polymer.
[0061] In the present invention, the second solvent is one or more of N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the second solvent ensures that the system is a uniform, transparent solution before and after the functionalization reaction. The concentration of the initial polymer solution is preferably 0.02 to 0.05 g / mL, more preferably 0.3 to 0.4 g / mL.
[0062] The cationic functionalized small molecule is preferably any one of a precursor molecule capable of generating quaternary ammonium salts, quaternary phosphonium salts, imidazolium salts, piperidinium salts and their derivatives, more preferably one or more of iodomethane, trimethylamine, N-methylimidazole and N-methylpiperidine;
[0063] The acid binding agent is one or more of anhydrous potassium carbonate, triethylamine, pyridine and diisopropylethylamine.
[0064] In the present invention, the molar ratio of the initial polymer to the cationic functionalized small molecule is (0.5-1):1, more preferably (0.6-0.8):1, such as 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, preferably a range value with any of the above values as the upper or lower limit; the molar ratio of the acid binding agent to the cationic functionalized small molecule is (1-4):1, more preferably (2-3):1.
[0065] In the present invention, the temperature of the functionalization reaction is preferably 25 to 120°C, more preferably 50 to 100°C, such as 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, preferably a range value with any of the above values as the upper or lower limit; the time of the functionalization reaction is preferably 1 to 3 days, more preferably 1 to 2 days.
[0066] After obtaining the anionic functionalized polymer, the present invention dissolves the obtained functionalized polymer in a third solvent to form a casting solution. The casting solution is then coated on a substrate, the solvent is slowly evaporated, and after sufficient drying and solidification, an anion exchange membrane is obtained. The obtained anion exchange membrane is then annealed and then slowly cooled to room temperature. During the solvent evaporation and annealing process, the polymer chain segments undergo chain folding self-assembly, forming a regular microstructure and ion channels, thereby obtaining an anion exchange membrane with a regular chain folding structure.
[0067] In the present invention, the third solvent includes one or more of N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide and N-methylpyrrolidone; the concentration of the casting solution is 0.005-0.2 g / mL, more preferably 0.01-0.15 g / mL, such as 0.005 g / mL, 0.01 g / mL, 0.015 g / mL, 0.02 g / mL, 0.03 g / mL, 0.04 g / mL, 0.0 5g / mL, 0.06g / mL, 0.07g / mL, 0.08g / mL, 0.09g / mL, 0.1g / mL, 0.11g / mL, 0.12g / mL, 0.13g / mL, 0.14g / mL, 0.15g / mL, 0.16g / mL, 0.17g / mL, 0.18g / mL, 0.19g / mL, 0.2g / mL, preferably a range value with any of the above numerical values as the upper or lower limit.
[0068] In the present invention, the solvent is preferably evaporated slowly at 25-60°C, more preferably at 30-50°C, such as 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, preferably within a range with any of the above values as the upper or lower limit.
[0069] In the present invention, the annealing temperature is preferably 60 to 120°C, more preferably 70 to 10°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, preferably a range value with any of the above values as the upper or lower limit. During the annealing process, the annealing temperature should be higher than the solidification temperature of the ion exchange membrane and lower than the melting point of the material. Annealing can eliminate stress in the material, promote the formation of chain folding structure, and make the microstructure and ion channel formed by the material more regular. The annealing time is preferably 1 to 5 hours, more preferably 2 to 4 hours.
[0070] The present invention provides an anion exchange membrane with a regular chain-folding structure, obtained by forming a membrane from a casting solution followed by annealing. The casting solution comprises a functionalized polymer having the structure shown in Formula 1. An anion exchange membrane with a regular chemical structure is designed and prepared by using an alkyl derivative with a certain number of methylene groups between two benzene rings as a monomer, which is then reacted with a ketone monomer via a Friedel–Crafts polymerization reaction. This anion exchange membrane has a fixed-length alkyl chain spacing between each functional unit. This regular chemical structure imparts unique chain-folding self-assembly behavior to the polymer segments. During the film-forming process, which is followed by solvent evaporation and curing, and annealing, the alkyl segments contained in the polymer segments spontaneously fold under the influence of crystallization, self-assembling into a regular chain-folding structure. Clear lattice fringes can be observed under high-resolution transmission electron microscopy. Furthermore, tests such as small-angle X-ray scattering and atomic force microscopy revealed that, due to differences in polarity, the functional groups are distributed around the periphery of the chain-folding structure, forming highly regular ion transport channels, enabling selective and efficient ion transport. In addition, by changing the chemical structure such as the length of the spacer alkyl chain, the length of the side chain, the type of functional group, etc., the morphology, size and function of the ion channel can be regulated. - The ion conductivity can reach over 30mS / cm, which is twice as high as the commercial anion exchange membrane AMV currently on the market. + and Mg 2+ The selectivity can reach more than 100, and the tensile strength can reach more than 30MPa.
[0071] In order to further illustrate the present invention, a chain-folded regular structure anion exchange membrane and a preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but it should not be understood as limiting the scope of protection of the present invention.
[0072] Morphology test
[0073] The microstructure and structure of the anion exchange membranes in the examples were examined using a transmission electron microscope (TEM; Hitachi, SU8220, Japan) and an atomic force microscope (AFM; Dimension Icon, Bruker Co.).
[0074] Tensile strength test
[0075] The tensile strength of the anion exchange membrane in the example was tested at room temperature using a dynamic mechanical analyzer (model: Q800, manufacturer: TA Instruments).
[0076] Ionic conductivity test
[0077] The anion exchange membrane obtained in the example was tested for ionic conductivity in a fully wet state using a four-electrode electrochemical impedance spectroscopy method. Specific test requirements and parameters were as follows: a membrane material with a length of 4 cm, a width of 1 cm, and a thickness of 40 μm was exchanged for the desired accompanying ions and then repeatedly washed with deionized water for 24 hours. An electrochemical impedance spectroscopy test was performed using an Autolab PGSTAT 30 electrochemical testing system at a frequency of 100 Hz to 1 MHz, and the ionic conductivity of the membrane in pure water was recorded.
[0078] Ion permeation test
[0079] The anion exchange membrane obtained in Example 1 was subjected to ion permeation experiments using a homemade U-shaped device. The device consisted of two tubular compartments with an inner diameter of 27 mm, separated by the tested membrane, with an effective area of 3.14 cm 2 One chamber was filled with approximately 50 mL of 0.1 M saline solution, serving as the feed side, and the same volume of deionized water was filled in the other chamber, serving as the permeate side. During the permeation experiments, both the feed and permeate chambers were stirred to avoid concentration polarization effects.
[0080] Example 1
[0081] This embodiment provides an anion exchange membrane with a regular chain folding structure, and its chemical structure is as follows:
[0082]
[0083] (1) Polymer Synthesis. 13.89 g (30 mmol) of 1,22-diphenyldocosane and 4.074 g (36 mmol) of N-methyl-4-piperidone were weighed into a 100 mL round-bottom flask. 15 mL of dichloromethane was added. 5 mL of trifluoroacetic acid and 3 mL of trifluoromethanesulfonic acid were slowly added dropwise at 0°C. The reaction temperature was lowered to -5°C and the reaction was allowed to proceed for 72 hours. The product was precipitated in a NaOH solution and washed thoroughly with deionized water. After filtration, a white solid was obtained, which was dried under ventilation at room temperature for 48 hours to obtain the initial polymer.
[0084] (2) Functionalization of the polymer. 5.58 g (10 mmol) of the initial polymer was weighed and dissolved in 200 mL of a mixed solvent of N-methylpyrrolidone and dimethyl sulfoxide. 2.764 g (20 mmol) of potassium carbonate was added and vigorously stirred at 60°C for 8 h. The reaction temperature was then lowered to 30°C, and 2.83 g (20 mmol) of iodomethane was added. The reaction was allowed to react at 30°C for 72 h. The reaction product was poured into acetone and precipitated to obtain a yellow precipitate. The precipitate was washed several times with acetone, then washed with water and dried to obtain an anionic functionalized polymer.
[0085] (3) Preparation of anion exchange membrane. Weigh 1 g of the above-mentioned anion functionalized polymer and add it to 20 mL of dimethyl sulfoxide. Stir vigorously at 80°C until it is completely dissolved. After centrifugation to remove impurities, a uniform and transparent casting solution is obtained. The resulting casting solution is coated on a glass plate and dried at 40°C to form a membrane. The solidified membrane is then heated to 80°C and maintained at this temperature for 2 h. The temperature is then slowly cooled to room temperature and the membrane is peeled off from the glass plate.
[0086] like Figure 2 As shown, the prepared anion exchange membrane exhibits distinct lattice fringes under a high-resolution transmission electron microscope, indicating that the polymer segments form a chain-folded crystalline structure. Due to differences in polarity, the functional groups are arranged around the periphery of the chain-folded structure, forming a regular ion channel.
[0087] like Figure 3 As shown, the formation of regular ion channels was observed by atomic force microscopy, and the darker area in the figure is the hydrophilic phase where the ion channels are located.
[0088] like Figure 4 As shown in the figure, the prepared anion exchange membrane has good mechanical properties, with a tensile strength of up to 30 MPa. The regular ion channels give the membrane excellent ion conductivity.
[0089] like Figure 5 As shown in the figure, the conductivity of the prepared anion exchange membrane for Cl- ions can reach 38mS / cm at 30°C. At the same time, the regular channel structure gives the membrane excellent ion selective permeability.
[0090] like Figure 6 As shown, the prepared anion exchange membrane has a + and Mg 2+ The permeation selectivity can reach 104.7.
[0091] Example 2
[0092] The only difference from Example 1 is that in the preparation process of the anion exchange membrane, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 1 is replaced with 12.21 g (30 mmol) of 1,18-diphenyloctadecane. The rest of the preparation method is the same as that of Example 1.
[0093] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 32 MPa, and the Cl - The ionic conductivity can reach 36mS / cm. + and Mg 2+ The permeation selectivity can reach 107.
[0094] Example 3
[0095] The only difference from Example 1 is that in the preparation process of the anion exchange membrane, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 1 is replaced with 11.3592 g (30 mmol) of 1,16-diphenylhexadecane. The rest of the preparation method is the same as that of Example 1.
[0096] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 33 MPa, and the Cl - The ionic conductivity can reach 35.4mS / cm. + and Mg 2+ The permeation selectivity can reach 105.4.
[0097] Example 4
[0098] The only difference from Example 1 is that in the preparation process of the anion exchange membrane, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 1 is replaced with 9.6762 g (30 mmol) of 1,12-diphenyldodecane. The rest of the preparation method is the same as that of Example 1.
[0099] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 34 MPa, and the Cl - The ionic conductivity can reach 33.5mS / cm. + and Mg 2+ The permeation selectivity can reach 106.
[0100] Example 5
[0101] The only difference from Example 1 is that during the preparation of the anion exchange membrane, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 1 was replaced with 7.9962 g (30 mmol) of 1,8-diphenyloctane. The rest of the preparation method was the same as that of Example 1.
[0102] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 36 MPa, and the Cl - The electrical conductivity of ions can reach 31.6mS / cm. + and Mg 2+ The permeation selectivity can reach 112.
[0103] Example 6
[0104] This embodiment provides an anion exchange membrane with a regular chain folding structure, and its chemical structure is as follows:
[0105]
[0106] (1) Polymer Synthesis. 13.89 g (30 mmol) of 1,22-diphenyldocosane and 6.7734 g (36 mmol) of 4-(trifluoroacetyl)toluene were weighed into a 100 mL round-bottom flask. 15 mL of dichloromethane was added. 15 mL of trifluoromethanesulfonic acid was slowly added dropwise at 0°C. The reaction temperature was lowered to -5°C and the reaction was allowed to proceed for 48 hours. The product was precipitated in a NaOH solution and washed thoroughly with deionized water. After filtration, a white solid was obtained, which was dried under ventilation at room temperature for 48 hours to obtain the initial polymer.
[0107] (2) Functionalization of polymer. Weigh 6.51 g (10 mmol) of the above initial polymer into 150 mL of chlorobenzene and stir vigorously at 130°C until completely dissolved. Add 1 equivalent of N-bromosuccinimide and azobisisobutyronitrile and react for 4 hours. Pour the reaction product into ethanol to precipitate a white precipitate, wash repeatedly, filter and dry to obtain a brominated polymer. Then weigh 2.136 g (3 mmol) of the above brominated polymer and dissolve it in 200 mL of N-methylpyrrolidone. Add 0.5852 (6 mmol) of N-methylpiperidine and 2.4877 g (18 mmol) of potassium carbonate and react at 100°C for 3 days. Pour the reaction product into ether to precipitate a yellow precipitate. Wash it with ether several times, then wash it with water and dry it to obtain an anionic functionalized polymer.
[0108] (3) Preparation of anion exchange membrane. Weigh 1 g of the above anion-functionalized polymer and add it to 20 mL of dimethyl sulfoxide. Stir at 80°C until completely dissolved. After centrifugation to remove impurities, the resulting casting solution is coated on a glass plate and dried at 40°C to form a membrane. The solidified membrane is then heated to 80°C and maintained at this temperature for 2 h. The temperature is then slowly cooled to room temperature and the membrane is peeled off the glass plate.
[0109] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 38 MPa, and the Cl - The ionic conductivity can reach 40mS / cm. + and Mg 2+ The permeation selectivity can reach 102.
[0110] Example 7
[0111] The only difference from Example 6 is that in the preparation process of the anion exchange membrane, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 6 is replaced with 12.21 g (30 mmol) of 1,18-diphenyloctadecane. The rest of the preparation method is the same as that of Example 6.
[0112] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 39.5 MPa, and the Cl - The ionic conductivity can reach 38mS / cm. + and Mg 2+ The permeation selectivity can reach 104.
[0113] Example 8
[0114] The only difference from Example 6 is that in the anion exchange membrane preparation process, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 6 is replaced with 11.3592 g (30 mmol) of 1,16-diphenylhexadecane. The rest of the preparation method is the same as that of Example 6.
[0115] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 43 MPa, and the Cl - The ionic conductivity can reach 36.5mS / cm. + and Mg 2+ The permeation selectivity can reach 108.
[0116] Example 9
[0117] The only difference from Example 6 is that in the anion exchange membrane preparation process, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 6 is replaced with 9.6762 g (30 mmol) of 1,12-diphenyldodecane. The rest of the preparation method is the same as that of Example 6.
[0118] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 46 MPa, and the Cl - The ionic conductivity can reach 34mS / cm. + and Mg 2+ The permeation selectivity can reach 115.
[0119] Example 10
[0120] The only difference from Example 6 is that in the anion exchange membrane preparation process, 13.89 g (30 mmol) of 1,22-diphenyldocosane used in step (1) of Example 6 is replaced with 7.9962 g (30 mmol) of 1,8-diphenyloctane. The rest of the preparation method is the same as that of Example 6.
[0121] The prepared anion exchange membrane can be observed under high-resolution transmission electron microscopy, lattice fringes, and regular ion channels under atomic force microscopy. The tensile strength can reach 47 MPa, and the Cl - The ionic conductivity can reach 32.5mS / cm. + and Mg 2+ The permeation selectivity can reach 121.
[0122] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A chain folding regular structure anion exchange membrane is prepared according to the following steps: A) polymerizing an alkyl derivative having a structure of Formula 7 and a ketone monomer by a Friedel-Crafts reaction in the presence of a first solvent and a superacid catalyst to obtain an initial polymer; In formula 7, x is an integer from 5 to 30; The ketone monomer is one or more of N-methyl-4-piperidone, 2,2,2-trifluoroacetophenone, indolone and 1,1,1-trifluoroacetone, and derivatives thereof; the molar ratio of the alkyl derivative to the ketone monomer is 1:(1-1.5); B) mixing the initial polymer, the second solvent, the cationic functionalized small molecule and the acid binding agent, and performing a functionalization reaction to obtain a functionalized polymer; The cationic functionalized small molecule is one or more of iodomethane, trimethylamine, N-methylimidazole and N-methylpiperidine; the molar ratio of the initial polymer to the cationic functionalized small molecule is (0.5-1):1; C) dissolving the functionalized polymer in a third solvent to form a casting solution, coating the casting solution to form a membrane, and annealing to obtain an anion exchange membrane with a regular chain folding structure; The annealing temperature is 60-120° C.; the annealing time is 1-5 hours.
2. The method for preparing the anion exchange membrane with a regular chain folding structure as claimed in claim 1, comprising the following steps: A) polymerizing an alkyl derivative having a structure of Formula 7 and a ketone monomer by a Friedel-Crafts reaction in the presence of a first solvent and a superacid catalyst to obtain an initial polymer; In formula 7, x is an integer from 5 to 30; B) mixing the initial polymer, the second solvent, the cationic functionalized small molecule and the acid binding agent, and performing a functionalization reaction to obtain a functionalized polymer; C) dissolving the functionalized polymer in a third solvent to form a casting solution, coating the casting solution to form a membrane, and annealing to obtain an anion exchange membrane with a regular chain folding structure.
3. The preparation method according to claim 2, characterized in that: The first solvent is one or more of dichloromethane, chloroform, and 1,2-dichloroethane; The catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid.
4. The preparation method according to claim 3, characterized in that: The volume ratio of the first solvent to the superacid catalyst is (0-3):1, and the ratio of the total molar amount of the alkyl derivative and the ketone monomer to the volume of the first solvent is (0.3-1) mol:100 mL.
5. The preparation method according to claim 4, characterized in that: The polymerization temperature in step A) is -10 to 30° C., and the polymerization time is 2 to 100 hours.
6. The preparation method according to claim 2, characterized in that: The second solvent is one or more of N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide and N-methylpyrrolidone; The acid binding agent is one or more of anhydrous potassium carbonate, triethylamine, pyridine and diisopropylethylamine.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the acid binding agent to the cationic functionalized small molecule is (1-4):
1.
8. The preparation method according to claim 7, characterized in that: The temperature of the functionalization reaction in step B) is 25 to 120° C.; the time of the functionalization reaction in step B) is 1 to 3 days.
9. The preparation method according to claim 2, characterized in that: The third solvent includes one or more of N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide and N-methylpyrrolidone; The concentration of the casting solution is 0.005-0.2 g / mL.
Citation Information
Patent Citations
Anion exchange membrane containing flexible chain segment and based on polymerization of piperidone and aromatic hydrocarbon as well as preparation method and application of anion exchange membrane
CN112175170A